Influence of the Heterogeneity of Spatial Distribution of Peripheral Radio Equipment of 4G/5G Networks on the Level of Electromagnetic Background Created in Buildings - V. I. Mordachev (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2023)
Known results of studies of the radio frequency electromagnetic background generated in buildings by electromagnetic radiation from the peripheral equipment of 4G/5G mobile communications, including equipment for massive machine-type communication/Internet of things (mMTC/IoT) and user’s devices for wireless telephony and data transmission, are based on the use of a model of uniform random distribution of this equipment over the building internal space. The adequacy of this model for the analysis of a number of 4G/5G scenarios is questioned due to the fact that, excluding user’s devices, the main part of the mMTC/IoT peripheral radio equipment located in buildings is distributed along the walls of the premises with a tendency to concentrate them near the intersections of flat surfaces of walls, floors and ceilings. Paper presents the results of comparative estimates of the average intensity of electromagnetic background inside building for different types of distribution of the set of point sources of RF electromagnetic fields over the building interior space: for their uniform distribution over internal space and for two types of heterogeneity of this distribution: for uniform distribution of sources over building internal surfaces and with their uniform distribution along the lines of intersection of these surfaces. Results of this analysis indicate a relatively small effect of the considered types of heterogeneity in the spatial distribution of radiation sources on the estimates of the electromagnetic background average intensity created by these sources inside the building, when using a technique based on the representation of the internal space of a building as a set of solid angles, which internal space separate sections are characterized by the constancy of the sources average space density and by the average conditions for radio waves propagation in the direction of the observation point.